Neuromodulation of the Pudendal Nerve Assisted by 3D Printed: A New Method of Neuromodulation for Lower Urinary Tract Dysfunction - Gu, Yinjun; Lv, Tingting; Jiang, Chen; Lv, Jianwei (Frontiers in Neuroscience, 2021)
Electrical stimulation of peripheral nerves by implanted electrodes is an effective treatment for certain pelvic floor diseases. As well as intravesical electrical stimulation, this predominantly includes stimulation of the sacral nerve, tibial nerve, and pudendal nerve. The pudendal nerve is one of the main nerves that stimulate pelvic floor muscles, external urethral meatus, and the anal sphincter and pelvic organs, and it may have effects on frequent urination, urgency, dysuria, and perineal pain. It is difficult to locate because of its anatomical course however, leading to difficulties fixing the electrode, which increases the difficulty of pudendal nerve electrical stimulation in clinical practice. In the current study 3D printing navigation was used to solve these problems. Combined with autopsy data and patient pelvic and nerve data, a personalized design was generated. Neural modulation of the pudendal nerve was achieved by implanting the lead with the guidance of 3D printed navigation. 3D printed navigation can maximize the phase II conversion rate, reduce the difficulty of surgery, shorten the operation time, reduce damage to additional organs and blood vessels, and increase the accuracy of electrode implantation, and it can be performed while the patient is awake. It is an accurate, reversible, efficient, and minimally invasive surgery.